Understanding Hokkien swear word use by non-Hokkien speakers in Singapore - Kwek, Nicole Xin Yi (2018)
Swearing is considered to be both taboo and emotive language. Studies by Dewaele (2004a & 2004b) suggest that emotional attachment is an important factor in determining whether swearing occurs in one’s first language. However, they do not discuss communities where people swear in languages that they do not speak. This study explores the use of Hokkien swear words by non- Hokkien speakers in Singapore, with ‘non-Hokkien’ referring to people who do not identify as Hokkien or speak Hokkien. This study was conducted using a qualitative approach, with the data collected via a questionnaire and a semi-structured interview. It aims to understand the reasons and motivations for why non-Hokkien speakers use Hokkien swear words as well as the social functions of such language use. The results suggest that there are two reasons for why non-Hokkien speakers use Hokkien swear words, namely its integration into the Singlish lexicon as well as environmental and social factors. They also suggest that intention and meaning are both important when swearing although the reasons differ. Finally, the use of Hokkien swear words has been found to be a means of displaying one’s Singaporean identity and is reflective of both the language policies, power dynamics, and social categories present in Singapore.